Reducing environment and enhanced productivity controlled the accumulation of organic matter in the Upper Yangtze Basin, South China during the Late Ordovician-Early Silurian - Bao, Yan-Jun; Sun, Yuan-Yuan; Zhang, Di; Yan, Jian-Fei; Men, Yu-Peng; Sun, Wei; Lin, Jia-Shan; Wan, You-Li; Kang, Jian-Wei; Wang, Wen-Hua; Zhaxi, Qiangba (Journal of Asian earth sciences, 2025)
[Display omitted] •Redox-productivity synergy governed organic enrichment in Upper Yangtze Basin during Ordovician-Silurian transition.•Pyrite framboid size documents water-column redox shifts during the Ordovician-Silurian transition.•Water column euxiniction is discriminated from the water/sediment interface anoxia.•Water-column anoxia directly enhanced organic accumulation. The Upper Yangtze Basin developed a set of widespread organic-rich shales during the period from the Late Ordovician to the Early Silurian. The mechanisms controlling the accumulation of organic matter are the subject of much controversy. In the present study, we used various geochemical data, including total organic matter content, mineral composition, and trace and major elements from Well Daoye 1 drilled in the northern Guizhou Province, to evaluate the factors controlling the accumulation of organic matter. The indices such as CIA, Al%, Ti%, U/Th, V/Cr, Ni/Co, U-EF, V-EF, Mo-EF, Cuxs, Nixs, Excess Si, C-vaule, Cu/Al, Ni/Al, Co × Mn, Zr/Cr and Zr/Al2O3 were calculated from these data to reconstruct the paleoclimate, terrigenous influx, seawater redox conditions, and paleoproductivity. Pyrite framboid size statistics were used as an additional proxy in this study to differentiate redox conditions between the anoxic state of the water column and the water/sediment interface. The results obtained from this study suggest that both the strongly reducing environment of the water column and the enhanced paleoproductivity played key roles in the widespread accumulation of organic matter. We found that the importance of these two factors in controlling the accumulation of organic matter varies under different circumstances through the Ordovician-Silurian transition in the Upper Yangtze Basin. Our study invites a case-by-case investigation when evaluating the controlling factors of organic matter accumulation in different settings.